Born standing up : a comic's life - Martin, Steve, 1945- (Scribner, 2007)
The author shares the stories of his years in stand-up comedy in a humorous memoir that recalls a first job selling guidebooks at Disneyland, his early magic and comedy act, his years of honing his craft, and the sacrifice, discipline, and originality it took to take him to the top.